TINGKAT ASUPAN ZAT GIZI DAN STATUS GIZI PENDERITA THALASSEMIA DI KABUPATEN BANYUMAS - Erna Kusumawati; Atikah Proverawati; Dyah Umiyarni Purnamasari; Sertiyowati Rahardjo (Kesmas Indonesia, 2015)
ABSTRACTThalassemia is a public health problem and is a hereditary blood disease that frequently occurs , it is due to the accumulation of iron due to transfusion , appetite and low socioeconomic status. The purpose of this study was to determine the determinants of nutritional consumption thalassemia patients . This study used a qualitative descriptive design. A total of 30 respondents participated in this study were taken by simple random sampling technique . Results of the study were mostly (83,3%) patients with thalassemia aged 6-16 years, the majority (73,3%) good nutritional status. Levels of nutrient intake compared with the results obtained in 2013 AKG energy (60,0%) , protein (53,3%), calcium (100 %), iron (60,0%), phosphorus (73,3%), vitamin C (80%), Vitamin B (100%) deficit category < 70 % of the RDA of 2013, only vitamin A which are all included both categories. The increasing age will have a tendency to decline in nutritional status . In the quality of life of patients with thalassemia major effort needs to be improved understanding of the importance of nutrient intake to maintain iron levels in the bodyKeywords: thalassemia, nutritional status, Banyumas Kesmasindo, Volume 7( 2), Januari 2015, Hal. 153-166